Performance of oil and gas service provider based on dividend policy from 2000 – 2009 (SapuraCrest Petroleum Bhd, Petra Perdana Bhd, & Eastern Pacific Industrial Corp. Bhd) / Mohd Fadhil Mistar - Mistar, Mohd Fadhil (Faculty of Business and Management, 2010)
This report has been done to study the performance of Oil and Gas Service Provider in Malaysia. This study using some sources like secondary data and other approaches such as financial ratios has been use as a data collection. The data is taken from external sources such as journal, internet, data base and internet. This paper examines the dividend policy for public listed companies in Malaysia by identifying the financial and performance factors that influence the dividend policy of Malaysian oil and gas services provider. It also studies the different characteristics of dividend payout. Only SapuraCrest able to pay dividend only for 4 years that are in 2004, 2007, 2008 and 2009, while another 2 companies able pay dividend every years. Dividend distribution of Sapura very low because they did not give dividend to their shareholder but the trend becomes upward after 2003 till 2009. Eastern Pacific tend to the most stable company compare others, because they manage to give higher dividend per share, dividend payout ratio, dividend yield and ROI. While Petra Perdana, I find that they give constant dividend to their share holder. Profitability, as measured by ROA and ROE, shows stronger positive linear relationship with dividend yield and dividend payout ratio as compared to growth opportunities factor and firm size. On the contrary, firm leverage and firm risk show negative relationship with both dividend yield and dividend payout ratio. The dividend policy for these companies is rigid and sticky as managers are reluctant to cut or avoid omit dividend even when the performance of the companies are deteriorating. Management cutting dividend is always in a danger, because dividends policy gives very important information or signal to investor. If firms decide to cut their dividend, it will make the investor lost think twice to invest in the firm. High dividend will attract more investor to invest in certain firm. Dividend also important to balance between the growth of the company and the distribution to the shareholders Low dividend give critical influence on the value of the firm. The market price gets affected if dividends paid are less. A high dividend is not always a sign of good management.